2021
DOI: 10.1136/tsaco-2021-000744
|View full text |Cite
|
Sign up to set email alerts
|

Improving length of stay on a trauma service

Abstract: BackgroundReducing length of stay (LOS) is a major healthcare initiative. While LOS is closely linked to the diagnosis and procedure in elective surgery, many additional factors influence LOS on a trauma service. We hypothesized that more standardized patient management would lead to decreased LOS.MethodsRetrospective analysis of Trauma Registry data compared LOS before (PRE) and after (POST) implementation of standardized processes on a trauma service. Patients were subdivided by age (over and under 65 years)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…To provide optimal care to injured patients, trauma centers should identify ways to enhance the discharge process to improve throughout, facilitate posthospitalization care, and prevent readmission. A comprehensive, multidisciplinary discharge planning process can improve patient outcomes and decrease length of stay (Bardes et al, 2017;Biffl et al, 2021;Collins et al, 2014) and reduce the incidence of readmission and complications (Coffey et al, 2019). In a prospective study of patients discharged from a general medical service at a tertiary hospital, Forster et al (2003) found that 20% of patients had adverse events after discharge, many of which were preventable.…”
mentioning
confidence: 99%
“…To provide optimal care to injured patients, trauma centers should identify ways to enhance the discharge process to improve throughout, facilitate posthospitalization care, and prevent readmission. A comprehensive, multidisciplinary discharge planning process can improve patient outcomes and decrease length of stay (Bardes et al, 2017;Biffl et al, 2021;Collins et al, 2014) and reduce the incidence of readmission and complications (Coffey et al, 2019). In a prospective study of patients discharged from a general medical service at a tertiary hospital, Forster et al (2003) found that 20% of patients had adverse events after discharge, many of which were preventable.…”
mentioning
confidence: 99%